2010
DOI: 10.1111/j.1600-0528.2010.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Root caries risk indicators: a systematic review of risk models

Abstract: Objective-To identify risk indicators that are associated with root caries incidence in published predictive risk models.Methods-Abstracts (n=472) identified from a MEDLINE, EMBASE, and Cochrane registry search were screened independently by two investigators to exclude articles not in English (n=39), published prior to 1970 (none), or containing no information on either root caries incidence, risk indicators, or risk models (n=209). A full-article duplicate review of the remaining articles (n=224) selected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 55 publications
8
95
3
7
Order By: Relevance
“…Although coronal caries is more prevalent than root caries, root caries is an increasingly important clinical problem in dentistry, with an annual incidence of 27% among older adults (Griffin et al, 2004;Ritter et al, 2010). Nonetheless, little research emphasis is given to preventing caries in adults and, specifically, to preventing root caries.…”
mentioning
confidence: 99%
“…Although coronal caries is more prevalent than root caries, root caries is an increasingly important clinical problem in dentistry, with an annual incidence of 27% among older adults (Griffin et al, 2004;Ritter et al, 2010). Nonetheless, little research emphasis is given to preventing caries in adults and, specifically, to preventing root caries.…”
mentioning
confidence: 99%
“…The results revealed that the mean number of coronal decayed, missing, or filled tooth surfaces (DMFS) was 2.43, and that the mean number of root DFS was 0.43 in the placebo group. A systematic review 7) by Ritter et al reported that the incidence of root caries could be predicted by risk models, and that the most frequently described predictors of the incidence of root caries in published studies on risk models were the prevalence of root caries, the number of teeth, and the plaque index. Another report 1) , on the other hand, noted that the factors related to root caries differed more for middle-aged adults (aged 45-64 years) than for older adults (>65 years).…”
Section: Discussionmentioning
confidence: 99%
“…: mucosa, saliva) and the risk of infection from an oral source are not identified. Periodontal attachment loss may be a good predictor of root caries incidence (29), but it is not assessed with the DMFT index.…”
Section: Discussionmentioning
confidence: 99%